2006
DOI: 10.1007/s11240-006-9149-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of polyamines on in vitro anther culture of Citrus clementina Hort. ex Tan

Abstract: The improvement of the induction rate in Citrus anther culture is important for taking practical advantage of the haploid potential in breeding. The influence of polyamines on anther culture of Citrus clementina, cv Nules, with particular attention to the free, soluble and insoluble-conjugated polyamine levels, has been investigated. Putrescine, spermidine and putrescine plus spermidine, were added to the standard induction medium. Before culture, spermidine was the most abundant among the free polyamines dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 37 publications
(40 reference statements)
2
32
0
3
Order By: Relevance
“…However, putrescine was more efficient than spermidine and spermine in increasing callus induction in green plant regeneration in rice anther cultures of Taiper 309. The best concentration to increase green plant regeneration was 10 -3 M. Chiancone et al (2006), in their studies of androgenesis in clementines using putrescine, spermidine, and a mixture of both, achieved an improvement in the efficiency of androgenesis under the influence of spermidine. By contrast, putrescine did not positively affect the formation of embryos in Citrus clementina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, putrescine was more efficient than spermidine and spermine in increasing callus induction in green plant regeneration in rice anther cultures of Taiper 309. The best concentration to increase green plant regeneration was 10 -3 M. Chiancone et al (2006), in their studies of androgenesis in clementines using putrescine, spermidine, and a mixture of both, achieved an improvement in the efficiency of androgenesis under the influence of spermidine. By contrast, putrescine did not positively affect the formation of embryos in Citrus clementina.…”
Section: Discussionmentioning
confidence: 99%
“…An improvement in the efficiency of gynogenesis in onion has been achieved through the exogenous application of polyamines (Martinez et al, 2000;Geoffriau et al, 2006). The role of polyamines in androgenesis has been investigated by Tiainen (1992) in potatoes, Dewi et al (2004) and Dewi and Purwoko (2008) in rice, Kumar et al (2004) in cucumbers, Hema et al (2008) in niger (Guizotia abisinica L.), and Chiancone et al (2006) in clementines.…”
mentioning
confidence: 99%
“…Polyamines, which are involved in the control of numerous cellular functions, including free radical scavenging and antioxidant activity, have been found to confer protection from abiotic stresses Values are the means of 3 replicates ±SEM but their mode of action is not fully understood (Groppa and Benavides 2008). Polyamines have also been shown to play a role in cell culture induction, growth and development (Chiancone et al 2006;Santa-Catarina et al 2007;Steiner et al 2007). In sunflower, polyamines have been shown to increase dramatically in response to high Cd concentrations (1 mM) (Groppa et al 2007), which may be a mechanism of cell defense to the oxidative stress induced by Cd.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have indicated that 2,4-D help to enhance/promote callus growth while NAA and IAA supports direct embryogenesis (Liang et al 1987 ). The supplementation of medium with polyamines has also improved the frequency of embryos in clementine (Chiancone et al 2006 ), Cucumis sativus (Kumar et al 2004 ), and wheat (Rajyalakshmi et al 1995 ). Similar fi ndings in cereal anther culture have also been stated using arabinogalactans (Letarte et al 2006 ) and ovary co-culturing (Broughton 2008 ).…”
Section: Pretreatments and Media Compositionmentioning
confidence: 99%